Epidemiology of atrial fibrillation and risk of CVD mortality among hypertensive population: A prospective cohort study in Northeast China - Du, Zhi; Lin, Min; Tian, Yuanmeng; Jing, Li; Liu, Shuang; Li, Guangxiao; Jia, Tong; Sun, Qun; Shi, Lei; Sun, Jixu; Tian, Wen; Xing, Liying (Frontiers in Cardiovascular Medicine, 2022)
Background: Determining risk factors of cardiovascular disease (CVD)-related mortality and evaluating their influence is meaningful for effectively reducing corresponding mortality. However, few research findings have estimated the relationship between atrial fibrillation (AF) and CVD-related mortality among hypertension individuals. Objective: To investigate the epidemiology of AF in a hypertension population and determine the relationship between AF and CVD related mortality. Methods: Using a multi-stage, stratified, and cluster random sampling method, the prospective cohort study with a median follow-up of 3.51 years enrolled 10,678 hypertensive participants at baseline. The prevalence, awareness and anticoagulation data of AF in this focal population were carefully assessed. Stepwise logistic regression and cox regression analysis were respectively performed to evaluate determinants of AF and the association between AF and CVD-related mortality. Results: The overall prevalence of AF was 1.3% (95%CI, 1.1%–1.6%) in the hypertensive population, and it was higher in men than in women (1.8% vs 1.0%, respectively; p=0.001). The awareness of AF was 53.1%, and the rate of oral anticoagulant (OAC) therapy was only 4.2% although all AF participants should have required according to the European Society of Cardiology guidelines. The determinants of AF included elder, male and history of coronary heart disease in hypertensive population. Besides, compared with individuals without AF, the risk of CVD-related mortality significantly increased in hypertensive population with AF (HR 3.37, 95%CI 2.10-5.40). Conclusion: Our results indicated a huge burden of AF and underuse of OACs therapy for them in community-based hypertensive population. Considering that the mostly risk factors of AF were unmodifiable in hypertensive individuals, as well as its high risk of mortality, long-term interventions including AF education, timely screening, and widespread use of OACs should be emphasized in the focal populations.